Effectiveness of Cognitive-Behavioral Therapy on Depression, Anxiety, Negative Autonomic Thoughts, and Coping Strategies of Students - Golamikhah, Khadijeh; Abdolhosseini, Amir (International Journal of Applied Behavioral Sciences, 2025)
Background and Aim: Students often struggle with multiple mental health issues, and there is a need for effective, short-term treatment. Cognitive behavioral therapy is one of the most effective and well-known treatment approaches. The present study aims to investigate the effectiveness of cognitive behavioral therapy on depression, anxiety, negative autonomic thoughts, and coping strategies in students of Payam Noor University of Ilam. Materials and Methods: The research approach utilized was a quasi-experimental study characterized by a pre-test-post-test design alongside a control group. The statistical population for this study comprised all students enrolled at Payam Noor University of Ilam during the academic year 2023-2024. Among them, 30 people were selected purposefully and randomly assigned to two experimental (15 people) and control (15 people) groups. The research tools included the Beck Depression Inventory (second edition), Spielberg Anxiety Inventory, Negative Autonomic Thoughts Questionnaire (ATQ), and Endler and Parker Coping Strategies Questionnaire (1990). Cognitive-behavioral therapy (CBT) was used as an intervention method. Results: The findings of the analysis of variance with control of pre-test scores showed that the difference between symptoms of depression, anxiety, negative automatic thoughts, and coping strategies of the experimental and control groups was statistically significant (p<0.05). Therefore, cognitive behavioral therapy reduced symptoms of depression, anxiety, and negative automatic thoughts, and increased the number of coping strategies in students of Payame Noor University of Ilam in the experimental group compared to the control group in the post-test phase. The results showed that the eta square or the effect coefficient indicated that cognitive behavioral therapy caused (63% reduction in symptoms of depression, 32% reduction in anxiety, 21% reduction in negative automatic thoughts, and 24% increase in coping strategies) in students of Payame Noor University of Ilam. Conclusion: Therefore, it can be said that cognitive behavioral therapy can reduce problems related to students' mental health, including depression, anxiety, negative automatic thoughts, and coping strategies. It is recommended that university counselors use this approach to educate, prevent, and treat students.